Future Directions - Coffey, J. Calvin (Clinics in Colon and Rectal Surgery, 2022)
Recent findings related to the mesentery clarified the organisation of the abdomen at the foundational level. The Mesenteric-based model of abdominal anatomy articlulates a foundation that re-unites scientific and clinical approaches to the abdomen in health and disease. Importantly, recent advances are a reminder that we must always question dogma. The peritoneal-based dogma of conventional anatomy remained unquestioned for too long. With time, the mesenteric-based dogma will also be altered and improved on. Anatomy, and hence surgery, must always be considered as works in progress.
Keywords: mesentery; Future; Mesenteric Model of Abdominal Anatomy